Performance Analysis of IEEE 802.15.4 Based Wireless Sensor Networks using LAR protocol for CBR and ZIGBEE Traffic Applications - P., Samundiswary; R, Surender (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
IEEE 802.15.4 standard based wireless sensor networks (WSNs) emerges as the next generation wireless standard for low-rate wireless personal area networks. IEEE 802.15.4 standard offers low power, low data rate and short range networking for wireless battery powered devices. It has also started to demand much attention towards research. The performance of the network can be analysed by using different types of routing protocols. In this paper, the performance analysis of IEEE 802.15.4 based Wireless Sensor Networks is done by using Â Location Aided Routing (LAR) protocols for the traffic applications such as Constant Bit Rate (CBR) and Zigbee traffic application. The LAR protocol enables the routing of data between the source and destination by using directional flooding technique. The performance metrics such as throughput, delay, jitter and packets dropped of LAR for Â CBR and Zigbee traffic application is evaluated and analysed. The simulation is modelled by using QualNet.